Water quality study for Southern part of Al- Hammar marsh - AL-Shamary, A.Ch.; Yonis, K.H.; AL.Zawar, J.K. (Iraqi Journal of Aquaculture, 2022)
The Present study was Include some physical and chemical characteristics for east southern AL-Hammar marsh south of Iraq during November 2006 to November 2007 .The Samples were collected on monthly two stations, first AL-Nagarah and second ALBurgah, monthly change for temperature. The highest temperature value in august 30mºand 25mº for two station respectively, wheel lowest value in February 11mº to first station and January 10mº to second station. highest of salinity in Ogest 2 part thousand in first station and July 1.8 part thousand in second station, ammonia, Nitrite values were decreased generally and phosphates highest values, monthly changes for ecological characteristics in the first and second study, and all environmental characteristics monthly deferent between two station . The calculate coloration coefficient between physical and chemical characteristics. Positive and Negative relation. There were significant differences (F-test) (P<0.05) between two station respectively.